Loss of the nuclear pool of ubiquitin ligase CHIP/STUB1 in breast cancer unleashes the MZF1-cathepsin pro-oncogenic program - Luan, Haitao; Mohapatra, Bhopal C.; Bielecki, Timothy A.; Mushtaq, Insha; Mirza, Sameer; Jennings, Tameka A.; Clubb, Robert J.; An, Wei; Ahmed, Dena; El Ansari, Rokaya; Storck, Matthew D.; Mishra, Nitish K.; et al. (American Association for Cancer Research, 2018)
CHIP/STUB1 ubiquitin ligase is a negative co-chaperone for HSP90/HSC70, and its expression is reduced or lost in several cancers, including breast cancer. Using an extensive and well-annotated breast cancer tissue collection, we identified the loss of nuclear but not cytoplasmic CHIP to predict more aggressive tumorigenesis and shorter patient survival, with loss of CHIP in two-thirds of ErbB2+ and triple-negative breast cancers and in one-third of ER+ breast cancers. Reduced CHIP expression was seen in breast cancer patient-derived xenograft tumors and in ErbB2+ and triple-negative breast cancer cell lines. Ectopic CHIP expression in ErbB2+ lines suppressed in vitro oncogenic traits and in vivo xenograft tumor growth. An unbiased screen for CHIP-regulated nuclear transcription factors identified many candidates whose DNA-binding activity was up-or down-regulated by CHIP. We characterized Myeloid Zinc Finger 1 (MZF1) as a CHIP target given its recently identified role as a positive regulator of cathepsin B/L (CTSB/L)-mediated tumor cell invasion downstream of ErbB2. We show that CHIP negatively regulates CTSB/L expression in ErbB2+ and other breast cancer cell lines. CTSB inhibition abrogates invasion and matrix degradation in vitro and halts ErbB2+ breast cancer cell line xenograft growth. We conclude that loss of CHIP remodels the cellular transcriptome to unleash critical pro-oncogenic pathways, such as the matrix-degrading enzymes of the cathepsin family, whose components can provide new therapeutic opportunities in breast and other cancers with loss of CHIP expression.